Intended Near-Total Removal of Koos Grade IV Vestibular Schwannomas: Reconsidering the Treatment Paradigm. Issue 2 (5th April 2017) - Zumofen, Daniel Walter; Guffi, Tommaso; Epple, Christian; Westermann, Birgit; Krähenbühl, Anna-Katharina; Zabka, Susanne; Taub, Ethan; Bodmer, Daniel; Mariani, Luigi
Abstract: BACKGROUND: The goals of treating Koos grade IV vestibular schwannomas are to relieve brainstem compression, preserve or restore neurological function, and achieve long-term tumor control while minimizing tumor- and treatment-related morbidity. OBJECTIVE: To propose a treatment paradigm involving the intentional near-total removal of Koos grade IV vestibular schwannomas, in which a small amount of residual tumor is not dissected off the cisternal portion of the facial nerve. Patients are then followed by a wait-and-scan approach. Any subsequent volumetric progression of the residual tumor is treated with radiosurgery. METHODS: This is a case series of 44 consecutive unselected patients who underwent intended near-total resection of a Koos grade IV vestibular schwannoma through a retrosigmoid approach from January 2009 to December 2015. Pre- and postoperative volumetric analyses were performed on routine magnetic resonance imaging sequences (constructive interference in steady state and gadolinium-enhanced T1-weighted sequence). RESULTS: The mean preoperative tumor volume was 10.9 cm 3 . The mean extent of resection was 89%. At the last clinical follow-up, facial nerve function was good [House and Brackmann (HB) I-II] in 89%, fair (HB III) in 9%, and poor (HB IV-VI) in 2% of the patients. At the last radiological follow-up, the residual tumor had become smaller or remained the same size in 84% of patients. Volumetric progression was negatively correlated with the original extent of resection and positively correlated with postoperative residual tumor volume ( P = .01, P < .001, respectively). CONCLUSION: Intended near-total removal results in excellent preservation of facial nerve function and has a low recurrence rate. Any progressive residual tumor may be treated by radiosurgery.